Increasing Students' Understanding by Using ICT in Elementary Schools - Tusriyanto, Tusriyanto; Hikmah, Nurul; Intes, Amina; Nuraini, Rini; Pahmi, Pahmi (Journal International Inspire Education Technology, 2024)
This study aims to explore students' experiences in using information and communication technology (ICT) in learning and how it can improve their understanding in primary school. This research was conducted using a qualitative approach, involving 12 students from an elementary school in X city. Data were collected by in-depth interviews and observations, the collected data were then analyzed using content analysis method to identify patterns, themes, and meanings from the generated data. The results showed that the use of ICT in learning provides a positive experience for students and can improve their understanding in various subjects. Students experience changes in the way they acquire and process information, as well as in the way they interact with teachers and classmates. In addition, the use of ICT also motivates students to be more active in learning and improves their learning outcomes. However, there are some barriers that students face in using ICT in learning, such as technical difficulties and limited access. Therefore, this study concludes that the use of ICT in learning can improve students' understanding, but it needs to be balanced with efforts to overcome the barriers that arise. The conclusion of this study explains that the application of Information and Commucation Technology (ICT)-based learning media in schoolchildren